Implementasi E-Modul Berbasis Exe Learning pada Materi Puisi untuk Siswa Kelas VII MTs Sunan Kalijaga - Ubaidillah, A. Shafir; Werdiningsih, Dyah; Busri, Hasan (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
Learning media is a process that must exist to develop learning models in the independent curriculum, it is known that in class VII MTs Sunan Kalijaga, the learning media used are quite diverse, but the information technology facilities provided are not utilized properly, so teachers continue to make efforts to be able to utilize information technology in an appropriate manner. One of the Indonesian language teachers’ efforts is to implement e-modules based on Exe Learning, so the aim of this research is to be able to describe how to implement the use of e-modules based on Exe Learning on poetry material as well as the advantages and disadvantages of this learning media when implemented. This research model uses descriptive qualitative methods. The results of this research show that this Exe Learning based e-module is considered very effective because the use of this Exe Learning based e-module has several benefits for students and teachers and can increase students’ interest, creativity and learning motivation as well as improve student learning outcomes when carried out. test on poetry material. However, this application has several shortcomings which must also be developed further, namely that it must be used on a PC or laptop, making it difficult to access by students who do not have laptops/PCs outside of school